The Historicity of the Qur'an in Socio-Cultural of Arab Perspective - Muhamad Rifa’i Subhi (Postgraduate Program, Universitas Islam Negeri (UIN) K. H. Abdurrahman Wahid Pekalongan, Indonesia, 2017)
Most thinkers former Muslims are not able to escape the